PENERAPAN LEX SPORTIVA TERHADAP TINDAK PIDANA KELALAIAN MENYEBABKAN MATINYA ORANG PADA CABANG OLAHRAGA SEPAKBOLA - Sandy Yudha Baneran (2022)
Football has its own legal system which is created, enforced and run by the football institution, namely FIFA through a rule known as the Lex Sportiva doctrine, which is a transnational legal system because FIFA is a private international legal entity. On the other hand, the state also has its own legal system to manage state ownership, which is called the national legal system or positive legal system. Lex Sportiva as a transnational legal doctrine is binding on every member of FIFA. Uniquely, this doctrine can also be applied to a criminal act that occurs in the world of football as implicitly regulated in article 13 verse 1 (I) and (J) and article 13 verse 3 of the FIFA Statute. So if there is a crime that occurs in the sport of football, then it is not a legal basis that can be used to resolve the dispute, namely by using the Lex Sportiva doctrine, with positive law, namely Criminal Law. The author uses a normative juridical research method that uses library materials as the basis for studying approaches and also approaches to laws related to Lex Sportiva and criminal acts in sports. After the required data has been collected, the writer will then process the data using qualitative descriptive analysis techniques. That is by describing and interpreting the data that has been collected, so that it will obtain a general and comprehensive picture of the actual situation related to Lex Sportiva and criminal acts in soccer.